FLUKTUASI TINGKAT INFLASI, SUKU BUNGA DAN PRODUK DOMESTIK BRUTO TERHADAP TABUNGAN DI INDONESIA TAHUN 2005-2010 - Sari, Dita Kartika (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2012)
The research objective was to determine the progression rate of inflation, interest rates and gross domestic product of the savings from the years 2005-2010, to determine the magnitude of the effect of inflation rates, interest rates and gross domestic product of the savings. Analysis tools used in this study using multiple regression. Analytical results obtained are inflation, interest rates, gross domestic product is jointly affect savings. Based on this research, the implications of this research that the savings are affected by inflation, interest rates (SBI) and gross domestic product (GDP), while the rest is explained by other variables outside the model that is implicitly reflected in the variable.